Exercises of the short-foot as a method of pes planus treatment - Anna Karpińska; Bartłomiej Wrzesiński; Patrycja Łopatka; Edyta Piechocka (Kazimierz Wielki University, 2018)
The basic functions of the foot are: shock absorption, taking over the body weight, which determines the correct locomotion. Physiologically, the body weight is based mainly on three points of support: the first and fifth metatarsals bone and in the middle of the heel tumor. Improper arching of the physiological arches of the feet leads to the development of flat feet, which results in improper load distribution on the feet and overloads in all body structures. There are many diagnostic methods to diagnose flatfoot, among them we can distinguish: podoscopy examination and on a podobarography platform. One of the most effective methods of flatfoot treatment are the short- foot exercises. They are aimed at activating the short plantar muscles of the foot responsible for its proper arching. Exercises outside the regulation of muscle work also contribute to the improvement of proprioceptive sensation. Systematically and reliably conducted gymnastics have a beneficial effect on the shape of the feet.